Estudo da produção científica brasileira na área nuclear no período de 1970-1979 - Nascimento, Maria de Jesus (1983)
In order to know the patterns of Brazilian scientific production in the nuclear area, and by using the registers from 1970 to 1979 of the Date Base of CIN/INIS, it was agreed that all information created or/and published in Brazil should be considered as Brazilian production. For a more detailed study, production was, then, divided into three exclusive categories: papers created and published in Brazil, the so called Autoctone Category, papers created abroad and published in Brazil, denominated Inclusion Category, and papers created in Brazil and published abroad, denominated Evasion Category. It could then be defined, from the institution, which papers had been produced outside or insid Brazil, and thus an author from a Brazilian institution was considered as a Brazilian author and an author from a foreign institution was considered as a foreign author. The three cat egories were analysed by following the same methodologycal in terms of: annual production; work / authorship; subject areas; language of publication; kind of literature; author categories; institutions and their geographical distribution; and countries of publication. The results show that the production is growing, but not in such an acce·lerated rhythm and that 74,16% of Brazilian production had its origin and was published in Brazil; 8,80% was created abroad and published in Brazil and 17,04% was created in Brazil but published abroad. Physics and chemistry are the most productive areas in Nuclear Energy; half of this literature is written in Portuguese, but for Inclusion and Evasion there was a great predominance of English, followed by F·rench, Spanish, German, and though with lower percentages, even Russian. H alf of the literature of the Autóctone and Inclusion Càtegories is in the forro of short comunication, because of the full coverage that the CIN gives to the annual meetings of SBPC (Sociedade Brasileira para o Progresso da Ciência) - a Brazilian society for the progress science, - and 1/4 of the Inclusion category consists of conference papers. This shows that conferences, saninars, etc. are the best means of attracting foreign scientists and foreign papers. The high percentage of 84,84% of journals articles in the Evasion C ategory indicates that Brazilian authors publish their papers of least relevance to the' area in Brazil in diverse comunication means, and they publish their papers of "better" quality outside Brazil, in hope of greater penetration by the scientific community through periodicals of international renown. The Evasion of Brazilian publications was seen mostly in which countries the world scientific production, such as the United States of America, Holland, England, etc with special attention to cases of publication is Israel, Russia, sweden, Switzerland and Luxembourg. In spite of the fact that the number of authors is increasing there is a trena toward decreasing. The production, indicates that multiple - authorship is increasing, especially in the Evasion Category. The reduced production in the Evasion Category is possibly due to the fact that the internal national production is beginning to take root. When Brazilian authors publish in Brazil, they woik in collaboration with authors of institutions from various parts of Brazil, the co-authorships are more concentrated in groups of institutioris which are near each other from the same institution. Almost all of the Brazilian production is concentrated in the southeast region, more specifically in são· Paulo and Rio de Janeiro where traditional research institutions such as USP, UNICAMP, IPEN, PUC, CBPF, · UFRJ and CNEN are located. Although in low percentages nuclear research is being developed in all of Brazil, with studies in various regions, even in the isolated cases in Alagoas, Sergipe, Maranhão, Piauí e Amapá.